Understanding the Transcriptional Changes During Infection of Meloidogyne incognita Eggs by the Egg-Parasitic Fungus Purpureocillium lilacinum - Xu, Wen-Feng; Yang, Jia-Lin; Meng, Xiang-Kun; Gu, Zhi-Guang; Zhang, Qi-Lin; Lin, Lian-Bing (Frontiers in Microbiology, 2021)
The egg-pathogenic fungus Purpureocillium lilacinum parasitizes on nematode eggs, and thus, it is used as a good biocontrol agent against plant root-knot nematodes. However, little is known about the transcriptional response of P. lilacinum while infecting nematode eggs. This study presents the whole transcriptome sequencing of P. lilacinum and transcriptome-wide gene expression analysis of P. lilacinum upon infecting the eggs of Meloidogyne incognita compared to non-infecting controls. A transcriptomic library of P. lilacinum was used as reference gene set and six transcriptomic libraries of the non-infecting control and P. lilacinum infecting M. incognita eggs were constructed, respectively, comprising three biological replicates of each. A total of 1,011 differently expressed genes (DEGs) were identified in the infecting samples, including 553 up-regulated and 458 down-regulated genes compared to the non-infecting control samples. Furthermore, functional enrichment analysis exhibited that these DEGs were primarily involved in oxidative phosphorylation, oxidoreductase activity, and metabolic processes. Fifteen DEGs were randomly selected to verify the RNA sequencing results through quantitative real-time polymerase chain reaction (qPCR). The study focused on P. lilacinum genes that were strongly expressed upon infecting M. incognita eggs. These DEGs were primarily involved in detoxification, parasitic behavior, and nutritional utilization. This study contributes significantly to the understanding of the molecular mechanisms underlying the parasitic action of P. lilacinum on nematode eggs and provides a valuable genetic resource for further research on parasitic behavior of P. lilacinum. Notably, this study examined the transcriptomics of P. lilacinum infecting M. incognita eggs at only one time point. Since there were fungi at different stages of the infection process at that time point, the transcriptional profiles are not precisely examining one specific stage in this process.